2023
DOI: 10.1101/2023.11.12.23298428
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monitoring ESBL-Escherichia coliin Swiss wastewater between November 2021 and November 2022: insights into population carriage

Sheena Conforti,
Aurélie Holschneider,
Émile Sylvestre
et al.

Abstract: BackgroundAntimicrobial resistance (AMR) poses a global health threat, causing millions of deaths annually, with expectations of increased impact in the future. Wastewater surveillance offers a cost-effective, non-invasive tool to understand AMR carriage trends within a population.AimWe monitored extended-spectrum β-lactamase producingEscherichia coli(ESBL-E. coli) weekly in influent wastewater from six wastewater treatment plants (WWTPs) in Switzerland (November 2021 to November 2022) to investigate spatio-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…24 To our knowledge, this is the first study to report specific sociodemographic characteristics that may be associated with higher concentrations of clinically-relevant AR bacteria in wastewater. If reflective of the human burden of AR bacteria, 25 these data may be informative for adapting interventions in community settings. Comparisons to human conization and infection data are needed before wastewater data are leveraged to inform public health practice in this setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 To our knowledge, this is the first study to report specific sociodemographic characteristics that may be associated with higher concentrations of clinically-relevant AR bacteria in wastewater. If reflective of the human burden of AR bacteria, 25 these data may be informative for adapting interventions in community settings. Comparisons to human conization and infection data are needed before wastewater data are leveraged to inform public health practice in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Swiss study estimated that sampling at least once per month results in a 95% CI width below ±0.5%. 25 Second, we did not specifically account for recent rainfall or surface temperature in our statistical analyses, although we did account for sampling round in all statistical analyses in an effort to account for differing meteorological conditions across timepoints. Recent studies have found mixed impacts of recent rainfall and temperature on AR Enterobacterales concentrations in wastewater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation